The social construction of “Feeling of Burden”: Narrative on dependency and care in old age - Arroyo Rueda, María Concepción; Ribeiro Ferreira, Manuel (UANL. Facultad de Trabajo Social y Desarrollo Humano, 2012)
In a society in which ambivalent positions of old age coexist, suffering from limitations in the basic functions of the human being disrupts the identity of old people and the social perception that is held of them. The impact of the deterioration and the physical incapacity affects not only old adults but also those who take care of them; it entails repercussions of instrumental, emotional and social types. Within the social and subjective dimension of aging arise stereotypes and negative images from being considered dependent subjects; one of most important of these is the “feeling of being a burden”. During the in-depth interviews, the diverse implications of this negative image in advanced old age are identified in old adults and their carers in the city of Durango, Mexico. The analysis of narratives shows results pertaining to the interrelation between the subjective aspects of the identity, the beliefs, and the power of social discourses.